Le varietà italoalbanesi - Savoia, Leonardo M. (Linguistik Online, 2025)
The Italo-Albanian communities of Southern Italy were formed in the 15th century when whole populations migrated from the territory of Southern Albania due to Turkish pressure. Today we find 50 communities in which Albanian variety is still spoken. The history of these communities is lively and engaged on the political-literary front: the Arbëreshë intellectuals contributed with their ideas and their work to the Italian Risorgimento and to the Albanian Rilindja. The Italo-Albanian varieties are of the Tosco type; they faithfully maintain the original morphosyntactic and phonological structure, while presenting loans and forms of contact with the adjacent Romance dialects. The vitality of the Arbëreshë dialects is sensitive to Italian sociolinguistic conditions, subject to the strong pressure of the standard language. Law 482 protects the use and autonomy of minority languages according to the lines of the UN and the European Union.